Enhanced absorption of surface plasma wave by metal nano-particles in the presence of external magnetic field. (4th August 2015) - Deepika; Chauhan, Prashant; Varshney, Anshu; Singh, D B; Sajal, Vivek
Abstract: The absorption of surface plasma wave (SPW) by metal nanoparticles embedded on the metal surface is studied in the presence of an external magnetic field. As a surface wave of frequency propagates through nanoparticles, electrons start oscillating and anomalous absorption of energy takes place at resonance frequency, where is the plasma frequency of electrons inside the nanoparticles. The absorption of the surface plasma wave by the nanoparticles enhances significantly in the presence of a magnetic field at modified resonance frequency (where is the cyclotron frequency). The absorption constant is directly proportional to the cube of a nanoparticle radius and inversely proportional to the square of interparticle separation. Maximum absorption constant is achieved for gold nanoparticles of the radius with interparticle separation and normalized cyclotron frequency . These results are of direct importance in nanoparticle based magneto-plasma solar cells.